Lymphoid stromal cells—more than just a highway to humoral immunity. Issue 1 (24th May 2021) - Cinti, Isabella; Denton, Alice E
Abstract: The generation of high-affinity long-lived antibody responses is dependent on the differentiation of plasma cells and memory B cells, which are themselves the product of the germinal centre (GC) response. The GC forms in secondary lymphoid organs in response to antigenic stimulation and is dependent on the coordinated interactions between many types of leucocytes. These leucocytes are brought together on an interconnected network of specialized lymphoid stromal cells, which provide physical and chemical guidance to immune cells that are essential for the GC response. In this review we will highlight recent advancements in lymphoid stromal cell immunobiology and their role in regulating the GC, and discuss the contribution of lymphoid stromal cells to age-associated immunosenescence. Graphical Abstract: